Addressing gaps in the diagnosis of TB in children - J. Hoffmann; C.R. Horsburgh Jr (IJTLD Open)
Since 2000, efforts to develop new treatments for TB have been promising, but diagnosing TB, especially in children, remains a challenge. This issue of the Journal includes the first in a series of articles related to TB in children, highlighting new diagnostic tests that do not rely on sputum, and have great potential for improving diagnosis and treatment initiation. Key to a reduction in TB prevalence, experts are engaging with communities to find undiagnosed cases and combat the stigma of TB. International collaborations are also central to integrating novel diagnostics and providing support for these vulnerable populations.